2021
DOI: 10.1177/1833358321992683
|View full text |Cite
|
Sign up to set email alerts
|

Social media in health communication: A literature review of information quality

Abstract: Background: Social media is used in health communication by individuals, health professionals, disease centres and other health regulatory bodies. However, varying degrees of information quality are churned out daily on social media. This review is concerned with the quality of Social Media Health Information (SMHI). Objective: The review sought to understand how SMHI quality issues have been framed and addressed in the literature. Health topics, users and social media platforms that have raised health informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 150 publications
1
38
0
1
Order By: Relevance
“…Furthermore, there is a scarcity of literature that has outlined standards for high-quality health-related social media content that can be used to inform the development and selection of credible content. The research gap regarding information quality on social media has also been identified in 2 systematic reviews, which have both described the need for a suitable tool to evaluate the quality of social media content [25,26]. Therefore, the aim of this study was to develop Principles for Health-related Information on Social Media (PRHISM), which defines high-quality health-related information and can be used to evaluate the quality of health-related social media content posted by any public account across all social media channels.…”
Section: Objectivementioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, there is a scarcity of literature that has outlined standards for high-quality health-related social media content that can be used to inform the development and selection of credible content. The research gap regarding information quality on social media has also been identified in 2 systematic reviews, which have both described the need for a suitable tool to evaluate the quality of social media content [25,26]. Therefore, the aim of this study was to develop Principles for Health-related Information on Social Media (PRHISM), which defines high-quality health-related information and can be used to evaluate the quality of health-related social media content posted by any public account across all social media channels.…”
Section: Objectivementioning
confidence: 99%
“…Communication of high-quality health information via social media has potential benefits, such as increased accessibility of information, improved communication between health professionals and patients, and social and emotional support for patients [25]. However, social media health information is generally not of high quality, particularly in relation to cancer, diabetes, and dental care [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Population-based studies from many countries have shown a significant impact of social media use and consumption of tobacco and alcohol among adults ( 21 – 25 ). Addressing this situation is especially complex because electronic media has also become the main platform for sharing health-related information not only for general population, but also for public health institutions ( 26 , 27 ). Understanding the association between media use and tobacco and alcohol use is therefore of critical importance among health researchers and practitioners in all countries.…”
Section: Introductionmentioning
confidence: 99%